Auctions vs. Negotiations. - Bulow, J; Klemperer, P (National Bureau of Economic Research, 1994)
Which is the more profitable way to sell a company: a public auction or an optimally structured negotiation with a smaller number of bidders? We show that under standard assumptions the public auction is always preferable, even if it forfeits all the seller's negotiating power, including the ability to withdraw the object from sale, provided that it attracts at least one extra bidder. An immediate public auction also dominates negotiating while maintaining the right to hold an auction subsequently with more bidders. The results hold for both the standard independent private values model and a common values model. They suggest that the value of negotiating skill is small relative to the value of additional competition.